Translation, Cross-cultural Adaptation and Reliability Analysis of the Survey of Anxiety and Information for Dentists (SAID) among Brazilian Adolescents - Giovanna Burgos Souto Maior; Trícia Murielly Andrade de Souza Mayer; Michele Gomes do Nascimento; Linda Jones; Viviane Colares (Association of Support to Oral Health Research (APESB), 2021)
Objective: To translate, perform a cross-cultural adaptation and reliability analysis of the Survey of Anxiety and Information for Dentists (SAID) for use with Brazilian adolescents. Material and Methods: The SAID was translated into Brazilian Portuguese and back-translated to English. An expert committee compared both versions and examined their equivalence. Then, a face validation was performed with 10 adolescents. The SAID was applied in printed format with 25 questions. Participants answered and commented on the questions with a researcher to confirm the understanding and provide suggestions. The suggestions were implemented, and the expert committee approved the final version of the SAID in Brazilian Portuguese. The psychometric properties were tested with 60 adolescents aged 10 to 19 years. Participants answered the Brazilian version of the SAID before their first dental appointment and two weeks later to determine test-retest reliability. Reliability was analyzed by internal consistency analysis (Cronbach's alpha) and test-retest (ICC). Results: The instrument presented excellent reliability according to internal consistency (Cronbach's alpha = 0.77) and test-retest coefficients (ICC = 0.88; 95% CI: 0.81-0.93). The Kappa coefficients and the degree of agreement of the dichotomous questions indicated good reproducibility of the new version. Conclusion: The SAID translation, cross-cultural adaptation and reliability analysis were completed successfully. Thus, the Brazilian version of the SAID can be a useful survey tool for dental care of adolescent patients.